THE IMPACT OF LIVE VIDIO THE IMPACT OF LIVE AND FREE SHIPPING AND PAY LATER VOUCHERS ON ONLINE BUYING INTEREST AT SHOPEE - Haryanti, Intisari; Aryani, Feni; Mulya, khas Sukma (Politeknik Bisnis Indonesia, 2024)
The purpose of this study was to determine and analyze the effect of live video, free shipping promo and pay later on online purchasing decisions at Shopee. This study uses associative research using quantitative data sourced from primary data sources. The research instrument used in this study was a Likert scale questionnaire. The population used in this study were all Shopee users in the city of Bima whose exact number is unknown. Because the population is not known for certain, the Cochrane formula is used to determine the sample size in the unknown population, so that a sample of 96 people was obtained. the sample is Shopee users who have shopped using Shopee pay later and free shipping promos at least once. The data collection techniques used are observation, questionnaires, and literature review. The data analysis techniques used are validity tests, reliability tests, classical assumption tests (normality tests, multicollinearity tests, autocorrelation tests, heteroscedasticity tests), multiple linear regression analysis, multiple correlation coefficients, decision tests, f tests, and t tests. The results of the study show that live video, free shipping promos and pay later have a significant influence on online purchasing decisions on Shopee, both partially and simultaneously.